ChemInform Abstract: Synthetic Strategies Towards the Azabicyclo[3.3.0]‐octane Core of Natural Pyrrolizidine Alkaloids. An Overview. Issue 28 (June 2016) - Martinez, Sabrina T.; Belouezzane, Chiraz; Pinto, Angelo C.; Glasnov, Toma
Abstract: Review: 255 refs.